Therapeutic antibody engineering by high efficiency cell screening. Issue 2 (26th November 2013) - Doerner, Achim; Rhiel, Laura; Zielonka, Stefan; Kolmar, Harald
Abstract : In recent years, several cell‐based screening technologies for the isolation of antibodies with prescribed properties emerged. They rely on the multi‐copy display of antibodies or antibody fragments on a cell surface in functional form followed by high through put screening and isolation of cell clones that carry an antibody variant with the desired affinity, specificity, and stability. Particularly yeast surface display in combination with high‐throughput fluorescence‐activated cell sorting has proven successful in the last fifteen years as a very powerful technology that has some advantages over classical generation of monoclonals using the hybridoma technology or bacteriophage‐based antibody display and screening. Cell‐based screening harbours the benefit of single‐cell online and real‐time analysis and characterisation of individual library candidates. Moreover, when using eukaryotic expression hosts, intrinsic quality control machineries for proper protein folding and stability exist that allow for co‐selection of high‐level expression and stability simultaneously to the binding functionality. Recently, promising technologies emerged that directly rely on antibody display on higher eukaryotic cell lines using lentiviral transfection or direct screening on B‐cells. The combination of immunisation, B‐cell screening and next generation sequencing may open new avenues for the isolation of therapeutic antibodies with prescribed physicochemical and functional characteristics.